PENGARUH PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA KEUANGAN KOPERASI DI KABUPATEN KLUNGKUNG - Pradnyaswari, Luh Gede Diah Ary; Putri, I. G. A. M Asri Dwija (E-Jurnal Akuntansi, 2016)
Good Corporate Governanc (GCG) principles such as transparancy, accountability, responsibility, indepedency and fairness should be applicated in every aspect of business including cooperation to push the raising market which is efficient and transparent. This research is aimed to determined the effect of GCG toward working performance of finance which is measured by return on assets to the cooperation at Klungkung regency. This research applied data collecting, quisionaire and documentation. This reseacrh involved 78 cooperation as research samples at Klungkung regency. In this case, there were 3 volunteers taken from each cooperation to give response. That is taken purposive sampling method and double linear regression analysis with SPSS. Based on findings, it can be concluded that GCG principles has positif effects to ward working performance of cooperation finance.
Keywords: good corporate governance principles, cooperation, working performance of finance, return on assets